THE ROLE OF BLENDED LEARNING IN ENHANCING ENGLISH LANGUAGE TEACHING IN HIGHER EDUCATION - Jumanova Sabrina,; Ropijonov Nodirbek, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article investigates the role of blended learning in improving English language instruction in higher education. It explores the integration of online and face-to-face learning and its impact on the development of the four language skills: reading, writing, speaking, and listening. The research draws from both theoretical frameworks—such as constructivism and the Community of Inquiry—and practical results obtained through experimental work. Findings reveal that blended learning promotes active engagement, autonomous learning, and technological fluency, all of which contribute to more effective and inclusive language education.